2016
DOI: 10.1177/1548051816655991
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Influence of CEO Extraversion and Openness to Experience on Firm Performance

Abstract: Research about the impact of the CEO's personality on firm-level outcomes has been ambiguous, partly because the underlying mechanisms remain largely unexplored. Given that the individuals most strongly influenced by a firm's CEO are the top management team (TMT) members, this study focuses on the CEO-TMT interface as a salient intervening relationship. We hypothesize that CEO personality traits of extraversion and openness to experience would influence firm performance indirectly through TMT behavioral integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 98 publications
2
19
0
1
Order By: Relevance
“…Extraversion refers to a person's tendency to be sociable, gregarious, assertive, talkative, and active (e.g., Abatecola, Mandarelli, and Poggesi ). Extraverted leaders tend to have a preference for a high level of interaction, sharing key information, and focusing on generating solutions (Araujo‐Cabrera, Suarez‐Acosta, and Aguiar‐Quintana ; Barrick and Mount ; Judge, Heller, and Mount ). Moreover, they have been found to strive to influence others and to show their status and power (Barrick, Mount, and Judge ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Extraversion refers to a person's tendency to be sociable, gregarious, assertive, talkative, and active (e.g., Abatecola, Mandarelli, and Poggesi ). Extraverted leaders tend to have a preference for a high level of interaction, sharing key information, and focusing on generating solutions (Araujo‐Cabrera, Suarez‐Acosta, and Aguiar‐Quintana ; Barrick and Mount ; Judge, Heller, and Mount ). Moreover, they have been found to strive to influence others and to show their status and power (Barrick, Mount, and Judge ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Gow, Kaplan, Larcker and Zakolyukina (2015) even find a negative impact of extraversion on firm performance. However, other studies suggest performance benefits from an extraverted CEO via higher strategic flexibility or better management team integration (Nadkarni and Herrmann, 2010;Araujo-Cabrera, Suarez-Acosta and Aguiar-Quintana, 2017). It has also been shown that extraverted CEOs are more likely to succeed in acquisitions (Malhotra, Reus, Zhu and Roelofson, 2018).…”
Section: Extraversion As a Ceo Stereotypementioning
confidence: 99%
“…However, the vast majority of this research on the importance of extraversion for leadership has been conducted at lower levels of the organization (e.g. Araujo‐Cabrera, Suarez‐Acosta and Aguiar‐Quintana, 2017; Wang et al ., 2016), with limited research focusing on the importance of extraversion for leaders at the upper echelons.…”
Section: Introductionmentioning
confidence: 99%